Hubungan Volume Ambing Dengan Produksi Susu Sapi Perah Friesian Holstein (FH) Di BBPTU-HPT Baturraden - Widodo, Tri Agung Wahyu; Santosa, Setya Agus; Astuti, Triana Yuni (ANGON: Journal of Animal Science and Technology, 2019)
Background. This resesrch was aims to determine the relationship of udder volume with milk production of Friesian Holstein (FH) dairy cattle in BBPTU-HPT Baturraden. Materials and Methods. The material used in the resesrch was 50 dairy cattle lactation 1, udder volume measurement, and daily milk production record for 1 lactation period. The instrument used is a measuring instrument in the form of a metline to measure the length, width, and height of the udder as a basis for measuring udder volume. The resesrch was conducted by survey methods. The measured variables are udder volume and milk production. Results. The results showed an average of milk production is 3,554.77 + 912.94 liters/lactation. Regression and correlation analysis results showed a low relationship between udder volume and milk production with a correlation coefficient of 0.244. The results of regression analysis showed a negative relationship between the two variables as indicated by a decrease in milk production of 0.034 liters at each increase in the udder volume scale. Conclusion. Based on the results of the resesrch it can be concluded that the size of the volume or size of the udder does not affect the amount of milk production produced.